ADDRESSING HOMELESSNESS AND PROVIDING SUPPORT FOR INDIVIDUALS AND FAMILIES IN NEED - Sarah Musalam Alazmi, Muhaya Ali Khalifah Alotibi, Ahmed Sulaiman Alrayes,‏ Mohammed Sahan Matar Alotaibi, Khaled Saad Almotawa, Magbulaha Habas Matar Alshamri, Mohmmed Ali Saeed Albarrak, Nawaf Homoud Alotaibi,; Meshal Mohammed Thaar Alotaibi, Majed Mohammed Hamad Bin Sanad, Ali Ali O Almurikhi, Fahad Suliman Alsabr (Chelonian Research Foundation, 2022)
Service gaps sometimes hinder persons with a prior experience of homelessness from getting necessary resources and securing stable housing. This study investigates the self-reported usage of services and the service requirements of individuals who are currently homeless, based on data obtained from them. This research discovered that people vary in their use and ongoing need of assistance based on the factors they described as leading to their homelessness. The majority of respondents said that they were aware of available services via personal recommendations. They had challenges in obtaining these services owing to restricted transportation alternatives. Furthermore, they were more inclined to use services that were conveniently located, met their requirements, and provided respectful treatment. These results have implications for the creation of coordinated intake systems and the implementation and distribution of programs designed to help those who are homeless.